RELASI PEMBANTU PRESIDEN DALAM KABINET KERJA JOKOWI-JK - Istighfaro Anjaz Azizi; Suyudi Khomarudin; Umar Mubdi; Albert Sudirman (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractThe conflicts between Minister of Maritime and Natural Resources Rizal Ramli and vice president Jusuf Kalla in electricity projects, Minister of State-Owned Companies and Minister of Transportation regarding fast-train development, Minister of Energy and Mineral Resources and Minister of State-Owned Companies regarding management policy of Masela Block, are conflicts inside the circle of the President’s assistants. These conflicts are implications from the obscurity of positions and authorities of said assistants. The author then researched with juridical empiric method. Through this research, it is hoped that the effective formulation of relation between the President’s assistants can be found.IntisariPerselisihan antara Menko bidang Kemaritiman dan SDA Rizal Ramli terhadap Wapres Jusuf Kalla dalam proyek listrik, Menteri BUMN dan Menteri Perhubungan dalam pembangunan kereta cepat, Menteri ESDM dan Menteri BUMN dalam kebijakan pengelolaan Blok Masela merupakan perseteruan di lingkaran pembantu presiden. Perseteruan tersebut merupakan implikasi dari ketidakjelasan kedudukan dan wewenang para pembantu presiden. Penulis kemudian meneliti permasalahan ini dengan metode yuridis empiris. Melalui penelitian ini, diharapkan dapat ditemukan formulasi pengaturan dan upaya untuk mewujudkan relasi pembantu presiden dalam Kabinet Jokowi-JK yang efektif dan efisien.